Moderasi Beragama dalam Kearifan Lokal Toraja: Misa’ Kada Dipotuo, Pantan Kada Dipomate - Anthonius Michael; Lusia Nopita Pongtiangin; Cornelius Arnoltus (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Indonesia is a multicultural country because which consist of various ethnic groups, cultures, religions, and races. Nevertheless, Indonesia has a motto to unite these differences, namely "Bhineka Tunggal Ika". One of the Indoensian tribes is the Toraja tribe. The Toraja tribe is live in South Sulawesi Province and mostly domiciled in the Tana Toraja and North Toraja regencies. Toraja is one of the tourist destinations in Indonesia. Currently, Toraja area has been inhabited by many people from various regions outside of Toraja. However, the Toraja people still adhere to the motto, namely "Misa' Kada Dipotou, Pantan Kada Dipomate" (United we stand, divorced we fall). The data collection in this study used the literature review method. The conclusion of this study is that religious moderation is very important to be implanted in a multicultural or heterogeneous place, especially in the Toraja tribal community. Moderation is not a new thing in Toraja society, but has been practiced for a long time. This can be seen from the motto "Misa' Kada Dipotuo Pantan Kada Dipomate" (United We Stand, Divided We Fall). In fact, this motto is part of religious moderation that can be lived by the Toraja people from generation to generation to maintain inter-religious harmony, which is coloured by many differences but all in one.